Safety and Efficacy of Baseline Antiplatelet Treatment in Patients Undergoing Mechanical Thrombectomy for Ischemic Stroke: Antiplatelets Before Mechanical Thrombectomy - Klail, Tomas; Sedova, Petra; Vinklarek, Jan F; Kovacova, Ingrid; Bar, Michal; Cihlar, Filip; Cernik, David; Kočí, Lubomir; Jura, Rene; Herzig, Roman; Husty, Jakub; Kocher, Martin; et al. (Journal of vascular and interventional radiology, 2023)
PURPOSE: To investigate the safety and efficacy of baseline antiplatelet treatment in patients with acute ischemic stroke (AIS) undergoing mechanical thrombectomy (MT). MATERIALS AND METHODS: Baseline use of antiplatelet medication before MT for (AIS) may provide benefit on reperfusion and clinical outcome but could also carry an increased risk of intracranial hemorrhage (ICH). All consecutive patients with AIS and treated with MT with and without intravenous thrombolysis (IVT) between January 2012 and December 2019 in all centers performing MT nationwide were reviewed. Data were prospectively collected in national registries (eg, SITS-TBY and RES-Q). Primary outcome was functional independence (modified Rankin Scale 0-2) at 3 months; secondary outcome was ICH. RESULTS: Of the 4,351 patients who underwent MT, 1,750 (40%) and 666 (15%) were excluded owing to missing data from the functional independence and ICH outcome cohorts, respectively. In the functional independence cohort (n = 2,601), 771 (30%) patients received antiplatelets before MT. Favorable outcome did not differ in any antiplatelet, aspirin, and clopidogrel groups when compared with that in the no-antiplatelet group: odds ratio (OR), 1.00 (95% CI, 0.84-1.20); OR, 1.05 (95% CI, 0.86-1.27); and OR, 0.88 (95% CI, 0.55-1.41), respectively. In the ICH cohort (n = 3,685), 1095 (30%) patients received antiplatelets before MT. The rates of ICH did not increase in any treatment options (any antiplatelet, aspirin, clopidogrel, and dual antiplatelet groups) when compared with those in the no-antiplatelet group: OR, 1.03 (95% CI, 0.87-1.21); OR, 0.99 (95% CI, 0.83-1.18); OR, 1.10 (95% CI, 0.82-1.47); and OR, 1.43 (95% CI, 0.87-2.33), respectively. CONCLUSIONS: Antiplatelet monotherapy before MT did not improve functional independence or increase the risk of ICH.
Keywords: Thrombectomy; Stroke; Mechanical Thrombolysis; Brain Ischemia; výsledek terapie; Thrombolytic Therapy; ischemická cévní mozková příhoda; cévní mozková příhoda; trombektomie; Intracranial Hemorrhages; Clopidogrel; Ischemic Stroke; Humans; mechanická trombolýza; intrakraniální krvácení; Aspirin; trombolytická terapie; ischemie mozku; Treatment Outcome; klopidogrel; lidé